Effectiveness of Thrombolytic Therapy in Acute Embolic Stroke due to Infective Endocarditis - Siva P. Sontineni; Aryan N. Mooss; Venkata G. Andukuri; Susan Marie Schima; Dennis Esterbrooks (Stroke Research and Treatment)
Objective. To identify the role of thrombolytic therapy in acute embolic stroke due to infective endocarditis. Design. Case report. Setting. University hospital. Patient. A 70-year-old male presented with acute onset aphasia and hemiparesis due to infective endocarditis. His head computerized tomographic scan revealed left parietal sulcal effacement. He was given intravenous tissue plasminogen activator with significant resolution of the neurologic deficits without complications. Main Outcome Measures. Physical examination, National Institute of Health Stroke Scale, radiologic examination results. Conclusions. Thrombolytic therapy in selected cases of stroke due to infective endocarditis manifesting as major neurologic deficits can be considered as an option after careful consideration of risks and benefits. The basis for such favorable response rests in the presence of fibrin as a major constituent of the vegetation. The risk of precipitating hemorrhage with thrombolytic therapy especially with large infarcts and mycotic aneurysms should be weighed against the benefits of averting a major neurologic deficit.